Transmission-Lightning-Arrester : A Location Determination Using Tflash - M. I. Jambak; M. A. B. Sidik; Zolkafle Buntat; Z. Nawawi; R. F. Kurnia; Y. Z. Arief; A. A. Wahab; Z Ramli; M. E. Ramly (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
The high density of lightning occurrence in Malaysiahas caused problems to transmission and distribution electricalenergy. Normally, transmission overhead lines trip due to BackFlashover (BF) of lightning and shielding failures of earth wire.Therefore, a detailed lightning study is required to analyse thecorresponding lines and to determine the exact location ofTransmission Lightning Arrester (TLA). In this paper, a simulationof lightning study using TFlash software associated with theinstallation of (TLA) at 132 kV SSWW-BBST overhead linessystem located in Selangor, Malaysia is presented. By using theTFlash software the location of TLA has been determined